Diskurse des Kalten Krieges Eine andere österreichische Nachkriegsliteratur - Stocker, Günther (2017)
The study analyses Cold War discourses in Austrian post-war literature, a subject that so far has been neglected in Austrian literary history. Through extensive research, 50 mainly unknown or little acknowledged novels, stories, plays and scenes were discovered which discuss phenomena of the Cold War that defined the first post-war decades. The theoretical focus on New Historicism allows an analysis of a broad spectrum of thematic clusters, images, discursive constellations and narratives which are contextualised both in national and international Cold War discourse./ In 15 chapters, the study discusses the discursive patterns of more than 50 rather unknown books from Austrian literature from the period 1945 to 1966, such as constructions and imaginations of borders, fictive travels behind the Iron Curtain, the Gulag, and metaphors of disease and narratives of espionage. These discourse patterns are positioned within the context of the Cold War.